Maxillary sinus pneumatization following extractions: a radiographic study - Sharan, Arbel; Madjar, David (The International journal of oral and maxillofacial implants, 2008)
The aim of this study was to identify and measure postextraction maxillary sinus pneumatization using fixed reference lines on panoramic radiographs. One hundred fifty-two panoramic radiographs, each of a different subject, were used to measure superoinferior differences of the sinus floor position in dentate sites in comparison with contralateral edentulous sites. Fifty-eight pairs of panoramic radiographs, each pair of the same subject, were used to measure superoinferior differences of the sinus floor position in the same site before and 6 to 67 months after extraction. All measurements were performed using an interorbital line and 2 zygomatic process lines as reference lines. Statistical correlations between the amount of expansion of the sinus and the root classification, projection length, duration after extraction, type, and number of the extracted teeth were examined. Postextraction expansion of the sinus in an inferior direction occurred in both comparisons (2.18 +/- 2.89 mm for dentate versus contralateral sites and 1.83 +/- 2.46 mm for the same site pre- and postextraction). A considerable amount of expansion occurred after the extraction of teeth surrounded by a superiorly curving sinus floor (5.27 +/- 1.59 mm). A larger expansion was also measured after second molar extractions in comparison to first molars and in cases of extractions of 2 or more adjacent posterior teeth. Posterior maxillary tooth extraction caused an inferior expansion of the maxillary sinus in relation to fixed anatomic landmarks, thus proving the pneumatization phenomenon after tooth loss. Sinus pneumatization was identified after extraction of maxillary posterior teeth. The expansion of the sinus was larger following extraction of teeth enveloped by a superiorly curving sinus floor, extraction of several adjacent posterior teeth, and extraction of second molars (in comparison with first molars). If dental implant placement is planned in these cases, immediate implantation and/or immediate bone grafting should be considered to assist in preserving the 3-dimensional bony architecture of the sinus floor at the extraction site.